Construction Portfolio in Emerging Markets: Indonesia - Manurung, Adler Haymans; Manurung, Gerry Juan Carlos; Eprianto, Idel; Widjanarko, Wirawan; Hatibie, Ch. Indra W. P. (Journal of Management World, 2025)
This research aims to explore equity Portfolio using Elton Gruber, Markowitz, Market Capitalization, Equal Weighted, and Market as Portfolio and Using Stochastic Dominance. Monthly return used for period of 2015 to 2023.  Elton Gruber Method is the highest cumulative return from December 2014 until December 2023. Using Safety First for portfolio, the return is varying range of 3.577% to 13.22% that Equal Weighted is the highest return using Roy Criteria. Using First-Order Stochastic Dominance (FSD), Portfolio of Markowitz Method has stochastic dominance comparing to others portfolio. Market Variable has impact for all portfolio return but interest has impact to Equal Weighted and Elton Gruber Method.  Pandemic Era have only impact to Markowitz Method.